KUAT TEKAN DAN KUAT TARIK MORTAR SEBAGAI BAHAN GRAUT DENGAN FAS OPTIMUM PADA AGREGAT HALUS GRADASI KASAR - , ADITYA PERMANA S ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Grout is a mixture of water, cement, fine aggregate, and other admixture or other chemicals that can be solidified, as filler material,grout must meet the requirements for workability test. So it can flow and fill the intended void. For that purpose we need to do further research on the composition of the optimum grout using available materials and later produced grout that has desireable compressive strength and tensile strength as well pass the workability test. The first step in this research is to make sand with coarse gradation. Then determine the composition of the grout that pass the flow time requirement according to ASTM 939 and SNI 03-6808-2002 (approximately about 35 seconds) using a flow cone method to determine the optimum water cement factor. Using a grout that meets the requirement, concrete was made then tested itâs tensile strength and compressive strength. Result of flow time test, compressive strength test, and tensile strength test become a reference to determine the composition of grout to be used in construction. The results showed that the optimum flow time (approximately about 35 seconds) is achieved in the volume ratio of 1 cement : 1 sand with water cement factor 0.55 and flow time of 24.07 seconds . The highest compressive strength at 7 days and 28 days achieved by grout with volume ratio of 1 cement : 0.5 sand, 33.443 MPa and 43.541 MPa,so is the highest tensile strength at 28 days achieved by grout with volume ratio of 1 cement : 0.5 sand at 3.88 MPa.